2016
DOI: 10.1051/0004-6361/201629200
|View full text |Cite
|
Sign up to set email alerts
|

Accretion regimes in the X-ray pulsar 4U 1901+03

Abstract: Context. The source 4U 1901+03 is a high-mass X-ray pulsar than went into outburst in 2003. Observation performed with the Rossi X-ray Timing Explorer showed spectral and timing variability, including the detection of flares, quasi-periodic oscillations, complex changes in the pulse profiles, and pulse phase dependent spectral variability. Aims. We re-analysed the data covering the 2003 X-ray outburst and focused on several aspects of the variability that have not been discussed so far. These are the 10 keV fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
50
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 63 publications
23
50
2
Order By: Relevance
“…Furthermore, drawing general conclusions about these theories is statistically questionable as only observational data of a single source are used. In future work, a detailed study of the recently claimed accretion regimes in 4U 1901+03 (Reig & Milonaki 2016) and V 0332+53 (Doroshenko et al 2016) combined with the results by Reig & Nespoli (2013) for various sources could help clarify this question. It should be noted, however, that thorough analysis methods are required and systematic effects (caused by detector calibration and due to the conversion to luminosities) have to be taken into account as, e.g., discussed here.…”
Section: Accretion Regimes In Gro J1008−57mentioning
confidence: 86%
“…Furthermore, drawing general conclusions about these theories is statistically questionable as only observational data of a single source are used. In future work, a detailed study of the recently claimed accretion regimes in 4U 1901+03 (Reig & Milonaki 2016) and V 0332+53 (Doroshenko et al 2016) combined with the results by Reig & Nespoli (2013) for various sources could help clarify this question. It should be noted, however, that thorough analysis methods are required and systematic effects (caused by detector calibration and due to the conversion to luminosities) have to be taken into account as, e.g., discussed here.…”
Section: Accretion Regimes In Gro J1008−57mentioning
confidence: 86%
“…Moreover, by comparing its K magnitude with the right panel of Fig. 1 in Reig & Milonaki (2016) we note that it is located inside the box populated by blue supergiants. In fact, we found that the observed K and J magnitudes and the observed J −K color are compatible with a B0.5Ia spectral type supergiant star, for a distance of ∼ 8.8 kpc and a reddening of Av=7.2 mag.…”
Section: Search For Infrared Optical and Radio Counterpartsmentioning
confidence: 96%
“…A number of papers in the literature have suggested that the outburst or high state of short period BeXR systems occurs when the propeller mechanism temporarily ceases to operate and uninhibited accretion resumes (see e.g. Tsygankov et al 2016;Christodoulou et al 2016;Reig & Milonaki 2016, and references therein). These outburst events occur on short timescales, at least in part as response to surges in wind density, leading to brief outbursts from direct accretion.…”
Section: The Propeller Mechanismmentioning
confidence: 99%